Unique in utero identification of fetuses in multi-fetal mouse pregnancies by placental bi-directional arterial spin labeling (BD-ASL) MRI - Avni, Reut (2011)
Non-invasive imaging is a critical part of the study of developing embryos/fetuses, particularly in the context of alterations of gene expression in genetically modified animals. However, in litter-bearing animals such as mice, the inability to accurately identify individual embryo/fetus in utero is a major obstacle to longitudinal, non-invasive in vivo studies. Arterial Spin Labeling MRI (ASL-MRI) was adopted here to determine the fetal order along the uterine horns in vivo, based upon the specific pattern of dual arterial blood supply within the mouse uterine horns. Blood enters the mouse uterus cranially through the ovarian artery, and caudally through the uterine artery. Saturation slices were alternately placed on the maternal heart or on the bifurcation point of the common iliac artery, thereby saturating either downward inflow via the ovarian arteries, or upward inflow via the uterine arteries, respectively. Saturation maps provided a unique signature with highly significant correlation between the direction-dependent magnetization transfer and the position of the fetuses/placentas along the uterine horns. The Bi-Directional ASL-MRI (BD-ASL) method reported here opens possibilities to determine and pursue phenotypic alterations in fetuses and placentas in longitudinal studies of transgenic and knockout mice models, and for studying defects in placental vascular architecture.